Health Equity Considerations for Developing and Reporting Patient-reported Outcomes in Clinical Trials: A Report from the OMERACT Equity Special Interest Group - Petkovic, Jennifer (J Rheumatol, 2017)
OBJECTIVE: Despite advances integrating patient-centered outcomes into rheumatologic studies, concerns remain regarding their representativeness across diverse patient groups and how this affects equity. The Outcome Measures in Rheumatology (OMERACT) Equity Working Group aims to determine whether and how to address equity issues within the core outcome sets of domains and instruments. METHODS: We surveyed current and previous OMERACT meeting attendees and members of the Campbell and Cochrane Equity Group regarding whether to address equity issues within the OMERACT Filter 2.0 Core Outcome Sets and how to assess the appropriateness of domains, instruments, and measurement properties among diverse patients. At OMERACT 2016, results of the survey and a narrative review of differential psychosocial effects of rheumatoid arthritis (i.e., on men) were presented to stimulate discussion and develop a research agenda. RESULTS: We proposed 6 moments for which an equity lens could be added to the development, selection, or testing of patient-reported outcome measures (PROM): (1) recruitment, (2) domain selection, (3) feasibility in diverse settings, (4) instrument validity, (5) thresholds of meaning, and (6) consideration of statistical power of subgroup analyses for outcome reporting. CONCLUSION: There is a need to (1) conduct a systematic review to assess how equity and population characteristics have been considered in PROM development and whether these differences influence the ranking of importance of outcome domains or a patient’s response to questionnaire items, and (2) conduct the same survey described above with patients representing groups experiencing health inequities.